3-dimensional versus conventional laparoscopy for benign hysterectomy: protocol for a randomized clinical trial - Elise Hoffmann; Gitte Bennich; Christian Rifbjerg Larsen; Jannie Lindschou; Janus Christian Jakobsen; Pernille Danneskiold Lassen (BMC, 2017)
Abstract Background Hysterectomy is one of the most common surgical procedures for women of reproductive age. Laparoscopy was introduced in the 1990es and is today one of the recommended routes of surgery. A recent observational study showed that operative time for hysterectomy was significantly lower for 3-dimensional compared to conventional laparoscopy. Complication rates were similar for the two groups. No other observational studies or randomized clinical trials have compared 3-dimensional to conventional laparoscopy in patients undergoing total hysterectomy for benign disease. The objective of the study is to determine if 3D laparoscopy gives better quality of life, less postoperative pain, less per- and postoperative complications, shorter operative time, or a shorter stay in hospital and a faster return to work or normal life, compared to conventional laparoscopy for benign hysterectomy. Methods/design The design is a randomised multicentre clinical trial. Participants will be 400 women referred for laparoscopic hysterectomy for benign indications. Patients will be randomized to 3-dimensional or conventional laparoscopic hysterectomy. Operative procedures will follow the same principles and the same standard whether the surgeon's vision is 3-dimensional or conventional laparoscopy. Primary outcomes will be the impact of surgery on quality of life, assessed by the SF 36 questionnaire, and postoperative pain, assessed by a Visual Analogue scale for pain measurement. With a standard deviation of 12 points on SF 36 questionnaire, a risk of type I error of 3.3% and a risk of type II error of 10% a sample size of 190 patients in each arm of the trial is needed. Secondarily, we will investigate operative time, time to return to work, length of hospital stay, and - and postoperative complications. Discussion This trial will be the first randomized clinical trial investigating the potential clinical benefits and harms of 3-dimensional compared to conventional laparoscopy. The results may provide more evidence regarding the future place of 3-dimensional laparoscopy in the range of endoscopic approaches for benign hysterectomy. Trial registration This study is registered at ClinicalTrial.gov: NCT02610985 November 16th 2015. November 2015. The regional Ethical committee approved it on the 12. November 2015, approval number: SJ-498. Data handling was approved by the Danish Data Protection Agency: REG-109-2015 on the 13. November 2015.